2014
DOI: 10.1177/1938640014521831
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Avascular Necrosis of the Talus

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 21 publications
0
69
0
Order By: Relevance
“…In the systematic review by Gross et al ., data from 85 patients from 3 studies, all involving atraumatic AVN talus at an average followup of 48 months, showed significant improvement in postoperative functional scores. 33 The combined rate of progression averaged 28%, with benefits seen both in early and late (Stage I/II and Stage II/III) stages of the disease in precollapse stage. Relief of symptoms is usually seen in 3–6 months.…”
Section: Joint-sparing Treatments: When and Which?mentioning
confidence: 98%
See 3 more Smart Citations
“…In the systematic review by Gross et al ., data from 85 patients from 3 studies, all involving atraumatic AVN talus at an average followup of 48 months, showed significant improvement in postoperative functional scores. 33 The combined rate of progression averaged 28%, with benefits seen both in early and late (Stage I/II and Stage II/III) stages of the disease in precollapse stage. Relief of symptoms is usually seen in 3–6 months.…”
Section: Joint-sparing Treatments: When and Which?mentioning
confidence: 98%
“…The outcomes of core decompression in the treatment of early-stage AVN talus have been extremely satisfactory, especially when the cause is non traumatic. 11 12 33 This works by reduction in the intraosseous pressure and enhances revascularization in the necrotic zone, akin to the idiopathic variant of osteonecrosis of femur head. Although it is recommended upto Stage I and II of the disease, we believe that the initial Stage III without significant collapse of the dome (<1 mm) can be given a trial of core decompression because the only alternative may be to go for an arthrodesis or joint-sacrificing treatment.…”
Section: Joint-sparing Treatments: When and Which?mentioning
confidence: 99%
See 2 more Smart Citations
“…Osteonecrosis may occur throughout the skeletal system, including temporal bone (Vudiniabola et al , ), ribs (Nicholls et al , ), femoral head (Camporesi et al , ), humeral head (Gruson and Kwon, ), lunate (Lutsky and Beredjiklian, ), and bones of the foot (Gross et al , ; Callachand et al , ). The epidemiology of many types of osteonecrosis is less well characterized than for ORN, although non‐traumatic femoral head osteonecrosis cases are estimated to occur at an annual incidence of 1.91/100 000 in Japan with a male‐to‐female ratio of 2.1:1 (Ikeuchi et al , ).…”
Section: Non‐mandibular Osteonecrosismentioning
confidence: 99%